Tackling local organised crime groups: lessons from research in two UK cities - Crocker, Ruth (Trends in organized crime, 2019)
This study examines the nature and community-level impact of organised crime groups known to the police in three deprived, high-crime neighbourhoods in which a wide range of organised crime was evident. By doing so, we were able to identify how the groups in these areas were structured, who was involved and how they operated. A number of key group features emerged. We describe these features to provide insight into the workings of locally based organised crime groups and discuss the implications for how local practitioners tackle these offenders, disrupt their operation and protect local communities from the corrosive impact of organised crime.